PENGEMBANGAN MEDIA KARTU BERGAMBAR ELEKTRONIK PADA PEMBELAJARAN PKN KELAS V SEKOLAH DASAR - Miluwati, Miluwati; Sutrisna Wibawa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to produce electronic picture card media as a medium for Civics learning material for the practice of Pancasila values ​​and to find out the validation of this media in class V of elementary schools. The objects in this research were 33 class V students at SDN 3 Kalimanggis, Temanggung district. The type of method chosen in this research is the ADDIE method which consists of five stages including, analyzing the needs of teachers and students, designing products and compiling instruments, developing products and validating experts, testing them on students and evaluating. The data collection techniques used were through observation, interviews and questionnaires. This research produces a product in the form of electronic picture card media for fifth grade elementary school students. The results of media development trials were carried out with three experts, namely, media experts, material experts and language experts. Based on the test results, the product feasibility received an average score of 88.17% which was categorized as very good. Meanwhile, trials are carried out on students through one-on-one trials, small groups and field tests. Product feasibility was rated with an average score of 92.5% which was categorized as very good. This shows that this application is very suitable for use in Civics learning in elementary schools.